2022
DOI: 10.30773/pi.2021.0239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screen Time on Physical and Mental Health and Eating Habits During COVID-19 Lockdown in Lebanon

Abstract: Objective This study aimed to explore whether screen time and the screen type impacted various health aspects of children, including physical activity (PA), sleep quality, and eating habits. Additionally, we investigated whether children’s eating behavior while using electronic devices affects their physical and mental health.Methods We conducted an online survey asking for screen use (duration, type, and purpose), PA, eating habits, sleep problems, and level of depression. The participants were children betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…It is possible to summarize the various contributions in this article by following a few main themes: the psychological and physical outcomes of using and owning technological gadgets during COVID-19 ( Adachi et al., 2022 ; Camerini et al., 2022 ; Chen et al., 2021 ; Chen et al., 2022 ; Cowan et al., 2021 ; Guo et al., 2021 ; Hmidan, 2022 ; Limone and Toto, 2021 ; Werling et al., 2021a ; Serra et al., 2021 ); behavioral problems related to overuse of media during COVID-19 ( Li et al., 2021b ; Marfua, 2021 ); the relationship between eating and sleeping disorders and the use of media during the pandemic ( Kamaleddine et al., 2022 ; Kim et al., 2022 ; Kotrla Topić et al., 2021 ); the effect of media in groups of clinical and ADHD children ( Sciberras et al., 2022 ; Shuai et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible to summarize the various contributions in this article by following a few main themes: the psychological and physical outcomes of using and owning technological gadgets during COVID-19 ( Adachi et al., 2022 ; Camerini et al., 2022 ; Chen et al., 2021 ; Chen et al., 2022 ; Cowan et al., 2021 ; Guo et al., 2021 ; Hmidan, 2022 ; Limone and Toto, 2021 ; Werling et al., 2021a ; Serra et al., 2021 ); behavioral problems related to overuse of media during COVID-19 ( Li et al., 2021b ; Marfua, 2021 ); the relationship between eating and sleeping disorders and the use of media during the pandemic ( Kamaleddine et al., 2022 ; Kim et al., 2022 ; Kotrla Topić et al., 2021 ); the effect of media in groups of clinical and ADHD children ( Sciberras et al., 2022 ; Shuai et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, some studies focused on unhealthy eating habits. One study ( Kamaleddine et al., 2022 ) conducted a logistic regression analysis using food consumption while using media devices as a dependent variable. The significant independent variables that predicted children's habit of eating foods while using electronic devices were total time spent on screen ≥2 h, time spent on smartphone screen ≥2 h, sleep problems, the ownership of technological device, and not eating unhealthy foods (ibidem).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…56 Our result was in line with previous studies that reported increased time spent online was associated with depression, anxiety, and insomnia. [57][58][59] Furthermore, change in the household income has also been shown as a predictive factor for major depressive disorder. In our study, 31.9% reported change of income due to COV-ID-19, and they were 2.18 times more likely to have major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%